Pembuatan Jamu Kunyit Asam Dengan Komposisi Bahan Dasar Yang Berbeda Untuk Kesehatan Tubuh Bagi Ibu-Ibu PKK RT 04 Kelurahan Labuhan Ratu Bandar Lampung - Yulianty; Endang Linirin Widiastuti; Nuning Nurcahyani; Enur Azizah; Primasari Pertiwi (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Turmeric is a plant with numerous health benefits. The most commonly used parts are the rhizome and the leaves. Generally, people use the rhizome as a cooking spice. Given the curcumin content in turmeric rhizomes, it should be developed into health-promoting beverages, such as Turmeric and Tamarind Jamu. This herbal drink is excellent for maintaining health, so the community in RT 04 Labuhan Ratu, Bandar Lampung, needs training in making Turmeric and Tamarind Jamu. The well-balanced composition of Turmeric and Tamarind Jamu can provide benefits by adding a refreshing flavor. Following the training on making Turmeric and Tamarind Jamu, there was an increase in knowledge among the participants. The initial pre-test score was 62.5 and after the training, the post-test score increased to 85. This represents an increase of 22.5 points.